Dilemmas of social justice in the practice of internationalization at an Irish university - Scheidt, Leticia; Minescu, Anca (Journal of International Students, 2026)
Policies advancing social inclusion in Irish higher education face new challenges with increased recruitment of students from the Global South. This study explores how staff at a University of Sanctuary in Ireland navigate tensions between internationalization and social justice. Using reflective thematic analysis of interviews with 11 staff and senior managers, two main themes emerged: (1) paradoxes of internationalization (as a tool for diversity, humanitarianism, or commodification) and (2) dilemmas of social justice and sustainability. Participants highlighted border-bound definitions of inclusion and critiqued extractive models of internationalization that reinforce colonial and unsustainable practices. We argue, in line with critical internationalization studies, that different models of internationalization are needed to promote sustainable education, equity, and social justice in higher education.